The Highly Pure Neem Leaf Extract, SCNE, Inhibits Tumorigenesis in Oral Squamous Cell Carcinoma via Disruption of Pro-tumor Inflammatory Cytokines and Cell Signaling - Morris, Jay; Gonzales, Cara B.; De La Chapa, Jorge J.; Cabang, April B.; Fountzilas, Christos; Patel, Mandakini; Orozco, Stephanie; Wargovich, Michael J. (Frontiers in Oncology, 2019)
Oral squamous cell carcinoma (OSCC) is a deadly disease that comprises 60% of all head and neck squamous cell cancers. The leaves of the Neem tree (Azadirachta indica) have been used in traditional Ayurvedic medicine for centuries to treat numerous oral maladies and are known to have significant anti-inflammatory properties. We hypothesize that a highly pure super critical CO2 Neem leaf extract (SCNE) prevents initiation and progression of OSCC via downregulation of intra-tumor pro-inflammatory pathways, which promote tumorigenesis. Hence, we investigated the anticancer effects of SCNE using in vitro and in vivo platforms. OSCC cell lines (SCC4, Cal27, and HSC3) were treated with SCNE while inflammation, proliferation, and migration were analyzed over time. SCNE treatment significantly inhibited OSCC cell proliferation and migration and reduced MMP activity in vitro, suggesting its potential to inhibit tumor growth and metastasis. The preventive effects of SCNE in ectopic xenograft and 4NQO-1 (4-Nitroquinoline-1-oxide) carcinogen-induced mouse models of OSCC were also evaluated. Indeed, xenografted nude mice showed significant reduction of OSCC tumor volumes. Likewise, SCNE significantly reduced the incidence of tongue dysplasia in the 4NQO-1 OSCC initiation model. In both OSCC animal models, SCNE significantly depressed circulating pro-cancer inflammatory cytokines (host and tumor-secreted) including NFkB, COX2, IL-1, IL-6, TNFα, and IFNγ. In addition, we demonstrate that SCNE downregulates STAT3 and AKT expression and activity in vitro. We also demonstrate that the primary active component, nimbolide (NIM), has significant anticancer activity in established OSCC xenografts. Lastly, we show that SCNE induces an M1 phenotype in tumor associated macrophages (TAMS) in vivo. Taken together, these data strongly support SCNE as means of preventing OSCC via downregulation of pro-cancer inflammatory cascades and NIM as a potential new therapy for existing OSCC.